Nestling Phenology of Anseriformes in the Baikal Siberia Region, Russia - E. N. Badmaeva; I. Yu. Deulin; M. A. Gulyaeva; L. D. Bazarov; T. Z. Dorzhiev; Ja. M. Jamalutdinov (Юг России: экология, развитие)
Aim. The goal was to aggregate data on the nesting phenology of the range of Anseriformes in the Baikal Siberia region – using the example of Lake Baikal itself.Material and methods. In preparing the materials we used data from our own observations based on foot and car‐based survey assessments and that of other authors for the entire known period of bird research on Lake Baikal, including data from the literature. Standard ornithological visual methods of accounting, registration and description are used.Results. The ecology of Anseriformes nesting has been sufficiently studied, but information on the oviposition phenology is not generalized. During the nesting periods of Anseriformes on Lake Baikal (in particular) the laying of eggs occurs over an extended time period. This prolongation egg‐laying time is normal and is a response to the death of clutches from inundations as well as being a characteristic of some ducks which re‐nest repeatedly. These subsequently lead to a later taking to flight of young birds. Conclusion. The earliest clutches are found among mallard and ruddy shelduck from the end of April, when ponds are still ice‐bound, while the latest are laid up to midJuly by the European widgeon, the white‐winged scoter and the red‐breasted merganser. Mass oviposition of all species occurs in the period from mid‐May to mid‐June. Overall, the egg‐laying period of Lake Baikal Anseriformes lasts from 20 days to 3.1 months. The timing and period of egg‐laying depends on regional environmental conditions and the specifics of individual species’ ecology and biology. Although the general ovipositional time‐frame of Anseriformes regionally is prolonged, the period of mass egg‐laying is quite concentrated and occurs within a period of 20‐30 days.